International Council of Nurses representing nursing at the World Health Organization: COVID‐19, policy and holding politicians to account. (22nd September 2021) - Catton, Howard
Abstract: The International Council of Nurses is in a unique position to represent nurses at the World Health Organization, and its task has never been more urgent than this year. Amid the global COVID‐19 pandemic, the death rates of nurses and other health care workers are truly shocking, with around 115 000 deaths. However, many countries do not collect statistics on health and care workers' deaths and infections from COVID‐19, so the full extent of this awful situation is not known. At this year's World Health Assembly, the body that sets the World Health Organization's agenda for the following year, the International Council of Nurses' 50‐strong delegation voiced the concerns of nurses and ensured that the views and advice of nurses were heard by the World Health Organization's 194 member states' delegates. Here, the International Council of Nurses' Chief Executive Officer Howard Catton describes how the Council is influencing health and care policy worldwide. He urges nurses everywhere to hold their politicians to account.